Stubborn People Among the Coconut Trees: Soge Farmer Resistance in Nangahale Plantation, East Nusa Tenggara - De Porres, Martin Elvanyus (BHUMI: Jurnal Agraria dan Pertanahan, 2022)
Since PT KRISRAMA's permit for Right to Cultivate expired in 2013, a number of Soge local residents, namely Tana Ai ethnic, have occupied the coconut plantation in Nangahale, Flores, East Nusa Tenggara. They claimed back the access to the customary land of Nangahale which, before the colonial era, was the residence of their ancestors. They put up a certain amount of resistance against the plantation company which, nota bene, is owned by the Catholic church, the Diocese of Maumere. This study elaborates the strategy of resistance of the Soge local residents. The methods used were participant observation and semi-structured interviews conducted from August to October 2021. The data collected were in the form of conversations and observation on the daily activities of the local residents as well as reviews on historical literature in newspapers, books, magazines, journals, and the internet. The conversation and observation data were analyzed according to the context that occurred in the field in order to reveal the forms of resistance. This study found that the resistance of Soge farmers to the Catholic church's company was part of a sparring movement in the form of regaining access and splitting land in response to the actions taken by the company that sought to expand their territory even without renewal of the contract permit. Keywords: Catholic church, coconut, land control, Nangahale, resistance